e-Minat: A website-based application for small and medium enterprises solutions - Muhammad Aji Pangestu; Devara Putra Sajjana; Chntya Dwi Anggraini; Arif Dwi Prasetya; Muh Taufiq Nur Hidayat; Irwansyah Irwansyah (Community Empowerment, 2023)
The marketing efforts of Mrs. Tresia Eka Wahyuni's MSME Mami Donat are still limited, and they are continuously looking for locations that are appropriate for their budget. In addition, there are not many people are aware of it because of its location far away from urban regions. This PkM's goal is to expand the market and increase product sales. E-minat is a website-based application with an e-commerce system. The program is carried out in stages, including designing a website-based application system, testing activities using the blackbox method, and training on using the e-Minat application. The outcome of this program indicates that the e-Minat application might help in boosting the market and sales of MSMEs, particularly MSME Mami Donat and MSMEs in the Rawa Makmur Village.